An activity based on an inquiry-driven creative drama: "stray animals need some shade". (31st March 2021) - Mutlu, Ayfer
Abstract: This study aimed to develop, introduce, and conduct an inquiry-driven creative drama activity. The activity, for elementary students, related to the transmission of light and full shadow. In the activity, which consisted of a warm-up, dramatization, and evaluation stages, two inquiry-based experiments were added to the dramatization stage. Thus, the goal was for the students to discover and learn during the dramatization. In addition to the experiments, role-playing, role changing, and teacher in the role techniques were used in the dramatization stage. Stray animals were assigned as a subject to dramatize for the integration of values education into science education. The activity was applied with the participation of 23 fifth-grade students, and students kept a reflective journal at the end of the activity. Based on their journals, the students had very definite opinions about the activity and demonstrated that both a scientific objective (optimizing shadow size) and values objectives (empathy, social responsibility, animal rights and help for vulnerable animals) were achieved. This activity is practical and of value in the elementary science classroom.